P020 Epigenetic regulation of brain-derived neurotrophic factor (Bdnf) expression mediates the effects of anodal transcranial direct current stimulation (tDCS) on hippocampal synaptic plasticity and memory in mice. Issue 3 (March 2017) - Podda, M.V.; Cocco, S.; Mastrodonato, A.; Fusco, S.; Leone, L.; Barbati, S.A.; Colussi, C.; Livrizzi, G.; Ripoli, C.; Grassi, C.
Abstract : Question: Understanding the cellular and molecular mechanisms underlying tDCS action is critical for a rationale use of this technique in clinical settings. Here we investigated the effects of tDCS on hippocampal synaptic plasticity and memory focusing on epigenetic mechanisms affecting the expression of plasticity-related genes. Methods: Electrophysiological, behavioral and molecular indices of hippocampal plasticity were investigated following 20-min anodal tDCS delivered to awake mice. Results: Hippocampal slices from tDCS-mice showed greater long-term potentiation (LTP) at CA3-CA1 synapses compared to sham-stimulated controls. Enhanced LTP was associated with improved hippocampal-dependent learning and memory assessed by the Morris water maze and novel object recognition tests. Remarkably, all these effects persisted 1 week after tDCS. Real-time PCR, Western Blotting and chromatin immunoprecipitation experiments revealed that tDCS effects were due to an intracellular signaling cascade including: (i) increased phosphorylation of cAMP response element-binding protein (CREB); (ii) enhanced CREB binding to the Bdnf promoter I; and, (iii) recruitment of the histone acetyltransferase CBP (CREB-binding protein) leading to enhanced histone 3 acetylation on Bdnf promoter I. As a consequence, the expression of Bdnf exons I and IX mRNAs was increased in the hippocampi of tDCS mice along with Bdnf protein levels. Accordingly, molecular, electrophysiological and behavioral effects of tDCS were prevented by mice treatment with either the acetylation inhibitor, curcumin, or the Bdnf receptor TrkB antagonist, ANA-12. Remarkably, we found that tDCS enhanced glycogen synthase kinase-3 β (GSK-3 β ) phosphorylation at Ser9 that was prevented by ANA-12, thus suggesting that GSK-3 β inhibition plays a role in the tDCS-induced increase of hippocampal plasticity. Conclusion: Our findings show that anodal tDCS increases hippocampal LTP and memory via chromatin remodeling of Bdnf regulatory sequences leading to increased expression of this gene. These results lend support to the use of tDCS for prevention and treatment of brain diseases associated with impaired neuroplasticity.